2017
DOI: 10.14218/jerp.2016.00035
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Brain 5-HT7 Receptors in the Formation of Stress Adaptation in Mice

Abstract: Background/Objectives: Impairment of the ability to adapt to stress in animals may contribute to some stressrelated psychiatric disorders, such as anxiety and depression. A growing body of evidence has suggested that the brain's serotonin (5-HT) nervous system may play an important role in the etiology, expression and treatment of anxiety and depression. The aim of the present study was to examine whether brain 5-HT 7 receptors are involved in the formation of stress adaptation. Methods:Male ICR mice were eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Most recently, Takeda et al identified a relationship between 5-HT 7 activation and stress adaptation. In that study, a single exposure to 60 min of restraint stress caused a reduction in the head-dipping response in the hole-board test.…”
Section: Physiological Function and Therapeutic Potentialmentioning
confidence: 99%
“…Most recently, Takeda et al identified a relationship between 5-HT 7 activation and stress adaptation. In that study, a single exposure to 60 min of restraint stress caused a reduction in the head-dipping response in the hole-board test.…”
Section: Physiological Function and Therapeutic Potentialmentioning
confidence: 99%